Organizational and forensic aspects of the electronic evidence handling - O. V. Manzhai; А. О. Potylchak; І. А. Manzhai (Law and Safety)
This paper outlines the ways of handling the electronic (digital) evidence based on the experience of the Ukrainian law enforcement bodies. It focuses mainly on the issues related to formalization and examination of the content of the electronic crime traces. Particular attention is paid to improving the arrangement of work with electronic evidence. The authors substantiate their position that the ordinary police officers need to attain the skills and knowledge how to handle the electronic evidence. The authors maintain that the nature and the mechanism of formation of electronic data are such that one may consider them as a separate kind of evidence, and the forms of registration thereof defined in applicable laws of Ukraine are far from perfect at the present time. Therefore, the article focuses on specific features pertinent to handling of the responses of institutions, enterprises, organizations; the extracted images and data from media; data banks and combinations of the aforementioned. The proposed solutions take into account the experience accrued at the time of participation in the project from interaction between the higher educational institutions and the police in the context of crime investigations.